Fabrication of antimony doped tin (IV) oxide conductive glass. - Carmen, Feby Escanda (2010.)
Antimony doped tin oxide conductive glass slide (ATO-CG) was febricated using Chemical vapour deposition (CVD) based method developed in the laboratory. Three deposition parameters were considered: (a) concentration of antimony dopant, (b) amount of coating solution used, and (c) sintering temperature. Resistance was measured using a digital multitester and the percent transmittance was determined using Spectronic 21, UV-vis Spectrophotometer of UPV Department of Chemistry. The ATO-CG slide which gave the highest conductivity and transmittance for all the deposition parameters @0.29 percent Sb dopant, 2 mL Sn:Sb solution and 500 degrees centigrade ) was tested for its performance by exposing it to high frequency vibration and heat based on the operating condition used for Dye-Sentisized Solar Cell (DSSC)., Results obtained showed that a lower concentration of antimony dopant, R decreases while T increases as volume of Sn:Sb solution increases. At higher concentration of dopant, R increases while T decreases as volume of Sn:Sb solution increases. Increasing temperature causes a decrease in R and an increase in T but beyond 500 degrees centigrade the trend changes inversely. Doping os Sb could increase conductivity and transmittance at specific range of Sb concentration added, which was observed to be at 0.29 percent to 0.58 percent Sb concentration on this study. Results of the sonication and application of heat proved that ATO-CG slide can be used as component of DSSC because it offers high mechanical stability as well as good conductivity .
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Antimony tin oxide